The Role of Ni-Carboxylate During Catalytic Asymmetric Iodolactonization Using PyBidine-Ni(OAc)2 - Arai, Takayoshi; Kajikawa, Satoshi; Matsumura, Eri (Synlett, 2013)
The combination of a PyBidine-Ni(OAc)2 complex with a catalytic amount of iodine efficiently catalyzed asymmetric iodolactonization to generate chiral iodolactones with up to 89% enantiomeric excess. The formation of an intermediate Ni-carboxylate species from the alkenyl carboxylic acid is a key role in promoting the iodolactonization.
Keywords: asymmetric catalysis; iodolactone; nickel; carboxylate; ligands